Neural tube defects among new borns: a cross-sectional study - Kidane, Mahder; Sime, Yohanes; Gashaw, Anteneh; Chane, Getachew (Frontiers in Pediatrics, 2023)
Abstract Background: Neural tube defects are a major public health issue that contributes significantly to morbidity and mortality, particularly in low-income countries such as Ethiopia. In Ethiopia, particularly in the study setting, there is a paucity of data on the prevalence, magnitude, and associated factors of neural tube defects. As a result, the purpose of this study was to evaluate neural tube defects and associated factors in JUMC. Methods: This study was institution-based cross-sectional study conducted from June to September 2021. Data was collected using a structured questionnaire adapted from previous literature. Data were analyzed using SPSS version 26 software. Logistic regression analysis was performed to assess the association between dependent and independent variables. Independent variables with a p-value < 0.05 were taken as statistically significant with neural tube defects. Results: Prevalence of NTDs in this study was 3.6%. Preterm newborns with GA<34 AOR 2.9(1.2-9.7), newborns with birth weight b/n 1000-1499 AOR 5.2(1.1-9.4), born with weight b/n 1500-2499 AOR 2.1(1.3-8.7), exposure to smoke AOR 2.1(1.2-8.8), radiation AOR 6.8(1.3-14.5), at least one history of abortion AOR 10.1(7.2-21.0) and mothers with AED intake AOR 5.7(2.3-18.4) found to be associated significantly. Conclusion: The results indicated a significant frequency of neural tube abnormalities in newborns. The use of AEDs, abortion, and radiation have all been linked to those NTD cases. Pregnant women are advised to learn more about the need of beginning prenatal care as soon as possible because the aforementioned issues will be addressed during this treatment.